TINGKAT RELEVANSI DAN FAITHFUL REPRESENTATION LAPORAN KEUANGAN PERBANKAN SYARIAH DI INDONESIA - indriyana puspitosari (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2019)
According to PSAK there are two fundamental qualitative characteristics in financial statements, namely relevant and faithful representation. The use of accounting standards is expected to improve the quality of financial statements. This study aims to look at the level of relevance and faithful representation of financial statements at Islamic Commercial Banks in Indonesia in the period 2013-2017. The sample in this study is 11 Islamic Banks. The level of relevance is measured by the absolute predictive value while the proxy of faithful representation is by using the absolute value of the discretionary accrual. The results of this study are that there is phenomenon trade-off where when the level of relevance of a bank is high, the value of faithful representation is lower among other islamic banks.